29. STUDY ON CLINICAL AND PARA-CLINICAL CHARACTERISTICS AND EVALUATION OF EARLY RESULTS OF TREATMENT OF LUMBAR SPINAL DISC HERNIZATION USING THROUGH TUBE MICRODONCULAR ENDURING SURGERY AT CAN THO CENTRAL GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objectives: (1) To survey the clinical and paraclinical characteristics of patients with lumbar disc herniation treated at Can Tho Central General Hospital in 2020 - 2023. (2) To evaluate the early results of surgical treatment of lumbar disc herniation by microsurgical discectomy through a balloon tube at Can Tho Central General Hospital in 2020 - 2023.Methods: A retrospective study describing 35 patients diagnosed with lumbar disc herniation through clinical and paraclinical examination and indicated for microsurgical discectomy through a balloon tube at Can Tho Central General Hospital from January 2020 to December 2023.Results: In the study, there were 25 male patients, 10 female patients, with an average age of 44.77 ± 12.74 years. Manual labor occupations accounted for 77.14%. 100% of patients had back pain, radiating along the nerve roots. The type of disc herniation with ruptured fibrous sac and intact nucleus pulposus accounted for 74.29%, with fibrous sac remaining 14.29%, and migration 11.43%. 100% of patients had good wound healing after surgery. Early treatment results assessment according to Macnab at the postoperative time recorded a high rate of 94.29% in the group of patients with very good and good levels.Conclusion: Microsurgical discectomy through a dilator tube is a safe method with a low complication rate.
Keywords: disc herniation; microsurgical enucleation; Macnab score